Tuning nanoparticle uptake: Live-cell imaging reveals two distinct endocytosis mechanisms mediated by natural and artificial EGFR targeting ligand - Mickler, Frauke M.; Möckl, Leonhard; Ruthardt, Nadia; Ogris, Manfred; Wagner, Ernst; Bräuchle, Christoph (Nano Letters, 2012)
Therapeutic nanoparticles can be directed to cancer cells by incorporating selective targeting ligands. Here, we investigate the epidermal growth factor receptor (EGFR)-mediated endocytosis of gene carriers (polyplexes) either targeted with natural EGF or GE11, a short synthetic EGFR-binding peptide. Highly sensitive live-cell fluorescence microcopy with single particle resolution unraveled the existence of two different uptake mechanisms; EGF triggers accelerated nanoparticle endocytosis due to its dual active role in receptor binding and signaling activation. For GE11, an alternative EGFR signaling independent, actin-driven pathway is presented. © 2012 American Chemical Society.
CRIS-Team Scopus Importer:2024-09-09
Keywords: EGF receptor; gene therapy; Live-cell imaging; polyplexes; targeting